A Bubble-Based Drag Model at the Local-Grid Level for Eulerian Simulation of Bubbling Fluidized Beds. (27th October 2016) - Hong, Kun; Cao, Manqian; Ullah, Atta
Abstract : A bubble-based drag model at the local-grid level is proposed to simulate gas-solid flows in bubbling fluidized beds of Geldart A particles. In this model, five balance equations are derived from the mass and the momentum conservation. This set of equations along with necessary correlations for bubble diameter and voidage of emulsion phase is solved to obtain seven local structural parameters (u g e, u p e, ε e, δ b, u b, d b, anda b ) which describe heterogeneous flows of bubbling fluidized beds. The modified drag coefficient obtained from the above-mentioned structural parameters is then incorporated into the two-fluid model to simulate the hydrodynamics of Geldart A particles in a lab-scale bubbling fluidized bed. The comparison between experimental and simulation results for the axial and radial solids concentration profiles is promising.